2022
DOI: 10.1080/21645515.2022.2044257
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ attitudes, knowledge and practice towards vaccinating their children against COVID-19: a cross-sectional study

Abstract: The question of whether children should be vaccinated against COVID-19 is currently being argued. The risk-benefit analysis of the vaccine in children has been more challenging because of the low prevalence of acute COVID-19 in children and the lack of confidence in the relative effects of the vaccine and the disease. One of the most convincing arguments for vaccinating healthy children is to protect them from long-term consequences. The aim of this study was to assess Jordanian parents’ intention to vaccinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 45 publications
7
30
2
Order By: Relevance
“…The current study found low parental COVID-19 vaccine acceptance for children, with only 38.3% of parents reporting willingness to vaccinate their children against COVID-19. This finding was in line with those of studies conducted across different countries, including Jordan [ 24 ], Turkey [ 33 ], Australia [ 34 ], and the USA [ 35 ], and lower than figures reported in studies conducted in the UK [ 36 ], the USA [ 32 ], Saudi Arabia [ 11 ], Japan [ 37 ], Korea [ 38 ], China [ 39 ], Brazil [ 8 ], Italy [ 7 ], and Qatar [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The current study found low parental COVID-19 vaccine acceptance for children, with only 38.3% of parents reporting willingness to vaccinate their children against COVID-19. This finding was in line with those of studies conducted across different countries, including Jordan [ 24 ], Turkey [ 33 ], Australia [ 34 ], and the USA [ 35 ], and lower than figures reported in studies conducted in the UK [ 36 ], the USA [ 32 ], Saudi Arabia [ 11 ], Japan [ 37 ], Korea [ 38 ], China [ 39 ], Brazil [ 8 ], Italy [ 7 ], and Qatar [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the findings of an earlier study [ 24 ], our results revealed that stronger perceptions about the effectiveness of a COVID-19 vaccine for children significantly reduced parental vaccination refusal. Perceptions about COVID-19 vaccine effectiveness have also been associated with parents’ acceptance of vaccination against COVID-19 for their children in previous studies [ 10 , 11 ] and with COVID-19 vaccination acceptance in other population groups, including adults [ 41 , 42 , 43 ], university students [ 44 ], and healthcare workers [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations